Die Dordtse Leerreëls: "n Grammatika van geloofstaal gebore uit die nasie-staat-ideologie - Van Wyk, Tanya ca. 20./21. Jh. (HTS teologiese studies, 2015)
The grammar of faith language in the Canons of Dordt as a result of the nation-state ideology. This article aims to decipher the spirit of the notion ‘predestination’ codified in the Canons of Dordt. It reconsiders the relevance of these dogmatic propositions about predestination as a grammar of the faith language which originated in a very specific context, namely the political concerns and the religious convictions held in the uniting Dutch provinces as a nation-state. In this context Calvin’s views about predestination became instrumental to the establishment of an upcoming nationalistic ideology, based on different interpretations and perceptions of Calvin’s theology. Within the context of the Protestant Dutch resistance against the RomanCatholic Spanish-Habsburg hegemony, the Canons were formulated during the Synod of Dordrecht in 1618–1619 as a Calvinistic movement against the Remonstrants who were stigmatised as collaborators of the Spanish-Habsburg reign over the Netherlands. This article demonstrates that different receptions of Dordt heighten the dogmatic gap between the socalled liberal modernism of the Remonstrants and a strict confessionalism of neo-Calvinism which has influenced the present-day understanding of the Canons of Dordt. It is argued that the grammar of the Canons of Dordt needs to be understood against this background and the meaning of the faith language it reflects, interpreted accordingly.